Absconding Behavior and Management of Apis cerana F. Honeybee in Chitwan, Nepal - Pokhrel, S; Thapa, RB; Neupane, FP; Shrestha, SM (Journal of the Institute of Agriculture and Animal Science, 2006)
Twelve colonies of five-framed Apis cerana F. with about equal brood, hive storage and colony strength were prepared in November 2004 and the colony development parameters recorded. One-third of the colonies absconded in summer and about one-sixth in rainy season, while non-absconded colonies also slowed comb building, brood rearing, colony strength and hive storage in summer and rainy seasons. Feeding sugar candy and pollen substitute prevented absconding in May and July. Three weeks feeding in May resulted higher comb building (15.0%), higher brood rearing (158.8%), stronger colony strength (15.0%) and higher hive storage (171.2% honey, 270.9% pollen) in June. Those colonies having higher brood mite (Varroa jacobsoni Oud.) in winter absconded earlier. Key words: Apis cerana, absconding, brood mite, pollen substitute, colony management J. Inst. Agric. Anim. Sci. 27:77-86 (2006)